Hubungan Frekuensi dan Lama Latihan terhadap Kelenturan Otot Penari Modern - M Naufal Firdaus; Dona Marisa; Asnawati Asnawati (Homeostasis, 2019)
Abstract: Muscle flexibility is an important part of physical fitness, which is crucial in helping muscle strength, increasing movement efficiency, coordination, and preventing injury. Flexural muscles will make the fibers in the muscles accustomed to elongation. Therefore, flexible dancers can withstand a great deal of stress compared to dancers who are less flexible. This study aims to determine the relationship of frequency and duration of exercise to the flexibility of modern dancer muscles. This study used an observational analytic method with a crossectional approach. A sample of 30 people who met the inclusion criteria were taken using the purposive sampling technique. The research instrument was a questionnaire and sit and reach box. Data analysis using the Spearman test. The results showed that the frequency of exercise samples was mostly 2 times per week with a length of exercise of mostly 120 minutes. For the flexibility of the muscles the sample is mostly included in the good category. The relationship between exercise duration and muscle flexibility results in a value of ρ value = 0,000. The conclusions from this study indicate a significant relationship between the frequency and duration of training in the flexibility of modern dancers muscles Keywords: frequency of training, duration of training, muscle flexibility, modern dancers Abstrak: Kelenturan otot merupakan bagian penting dari kebugaran fisik, yang membantu kekuatan otot, meningkatkan efisiensi gerakan, koordinasi, dan mencegah cedera. Otot yang lentur akan membuat serat-serat pada otot terbiasa dengan pemanjangan. Karena itu, penari yang lentur dapat bertahan dalam stress yang besar dibandingkan dengan penari yang kurang lentur. Penelitian ini bertujuan untuk mengetahui hubungan frekuensi dan lama latihan terhadap kelenturan otot penari modern. Penelitian ini menggunakan metode observasional analitik dengan pendekatan crossectional. Sampel sebanyak 30 orang yang memenuhi kriteri inklusi diambil dengan teknik purposive sampling. Instrumen penelitian berupa kuesioner dan kotak sit and reach. Analisis data menggunakan uji Spearman. Hasil penelitian didapatkan frekuensi latihan sampel sebagian besar adalah 2 kali per minggu dengan lama latihan sebagian besar 120 menit. Untuk kelenturan otot sampel sebagian besar termasuk dalam kategori good. Hasil analisis menghasilkan nilai ρ value = 0,000. Kesimpulan dari penelitian ini menunjukkan adanya hubungan yang bermakna antara frekuensi dan lama latihan terhadap kelenturan otot penari modern. Kata-kata kunci: frekuensi latihan, lama latihan, kelenturan otot, penari modern